2017
DOI: 10.5350/dajpn2017300206
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of depressive symptoms and related variables with depressive symptoms in alcohol and substance abusers

Abstract: Investigation of depressive symptoms and related variables with depressive symptoms in alcohol and substance abusersObjective: It is aimed to evaluate the bonding and personality traits which are thought to affect the level of depressive symptoms in alcohol and substance abusers. Methods:The study sample consists of 289 patients diagnosed with alcohol and substance dependence, that have been followed up at inpatient or outpatient units of Ege University, The Institute on Drug Abuse, Toxicology and Pharmaceutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The participants in the present study had a mean depressive symptom score of 37.10 ± 9.39. Some studies have observed that most individuals with substance addiction have diagnoses of depressive disorders or higher levels of depressive symptoms than other individuals (Çıray et al, 2018; Keskin & Gümüş, 2017). The participants in the present study had slightly higher depressive symptom levels than what is considered a moderate level, and they were a risk group for depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants in the present study had a mean depressive symptom score of 37.10 ± 9.39. Some studies have observed that most individuals with substance addiction have diagnoses of depressive disorders or higher levels of depressive symptoms than other individuals (Çıray et al, 2018; Keskin & Gümüş, 2017). The participants in the present study had slightly higher depressive symptom levels than what is considered a moderate level, and they were a risk group for depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…First, individuals were asked to fill in an individual information form. This form was developed as a result of a literature review and included eight questions on the sociodemographic and substance use characteristics of the participants (Keskin & Gümüş, 2017; Kim & Kim, 2017). The first six questions asked for the individuals' sociodemographic variables, namely each person's age, gender, marital status, education level, income status, and living situation (i.e., who the person was living with at the time of the study).…”
Section: Methodsmentioning
confidence: 99%